Bone Fracture: Understanding, Therapies, and Rehabilitation - Mohd. Amaan Khan (International Journal of Orthopedic Nursing and Practices, 2023)
Bone fractures are common injuries that can significantly impact an individual's quality of life. This article presents a comprehensive examination of bone fractures, encompassing their origins, categorization, and potential ramifications. This review of literature explores various therapeutic approaches and rehabilitation strategies employed in the management of bone fractures. Surgical interventions, non-surgical treatments, and rehabilitation techniques are discussed, highlighting their effectiveness in promoting healing, restoring function, and preventing complications. The article emphasizes the importance of a multidisciplinary approach in providing comprehensive care for individuals with bone fractures, leading to optimal recovery and improved outcomes.
Keywords: Bone fracture; Complications; Rehabilitation; classification; surgical intervention